Not Just An Accountant : The Diary of the Nation's Conscience Keeper - Rai, Vinod (New Delhi Rupa, 2014)
Not just an accountant is an incisive, no-holds-barred account of Indiaś eleventh comptroller and auditor general and a symbol of the anti-corruption movement, Vinod Rai. Through a narrative, rich in anecdote and inside information, Rai sheds light on the major scams that shook the country. Among the case studies-chosen for the diversity of failures they highlight are - the procedural irregularities in the issuance of licenses for second generation spectrum allotment, the last minute quick-fixes in the conduct of the XIX commonwealth games, the loss of national resources while allocating coal blocks, the flouting of systems and the clear display of crony capitalism in the exploration of hydrocarbon and the tragic tale of civil aviation in India. Through these illustrations, Rai wishes to not only expose government malfeasance, but also probe the mandate of the CAG as a watchdog. Equally, he hopes to push for long-term solutions to corruption and bring home the urgent need for ethics-for the pursuit of excellence, accountability, probity and transparency within governments, the bureaucracy, corporate enterprises and public life.
Keywords: Biography / History : Comptroller and Auditor - General - India